Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Semangat Kerja Karyawan Pada PT. SKF Indonesia - Putri Mutiara; Ni Nyoman Sawitri; Adi Wibowo Noor Fikri; Dewi Puspaningtyas Faeni; Indah Rizki Maulia (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The research employs a quantitative approach using statistical methods, where the data consists of numerical values obtained through the use of questionnaires and surveys. The total population in the production department of PT SKF Indonesia is 255 employees, and the sampling is done using the Purposive Sampling technique with the Slovin formula to determine the sample. The sample used is 72 employees from the production department of PT SKF Indonesia. This study utilizes Smart PLS 3.0 software and conducts testing, including data analysis methods (descriptive and verificative), outer model testing for validity and reliability, inner model testing for R-Square (R2), Predictive relevance (Q2), and model fit testing (Goodness of Fit), as well as hypothesis testing including T-test (Partial) and F-test (Simultaneous). The results of this study, in partial, show that the workload variable has a P-Value of 0.001 or < 0.05, indicating that the workload has a positive influence on work enthusiasm. The working environment variable has a P-Value of 0.000 or < 0.05, signifying that the work environment has a positive influence on work enthusiasm. Lastly, the simultaneous results indicate that the workload and work environment variables have a positive and significant impact on work enthusiasm, with an F-value of 923.83 > F-Table 3.13 and a coefficient of determination (R2) of 96.4% in R-Square.